Penyuluhan Tentang Hipertensi dan Pembuatan Obat Non Farmakologi Dengan Rebusan Daun Seledri di Desa Purwodadi - Ahmad Zakiudin; Tati Karyawati; Andita Andita (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a condition characterized by elevated blood pressure, where the systolic pressure exceeds 140 mmHg and the diastolic pressure exceeds 90 mmHg. If not properly treated, hypertension can lead to severe complications, increased morbidity, and even mortality. This condition occurs when the heart works harder than usual to pump blood (systolic) and the blood flow returning to the heart (diastolic) also experiences increased pressure. One of the efforts to prevent the progression of hypertension from a primary to a secondary stage is through non-pharmacological treatments. One such treatment includes the use of natural remedies like celery leaves. Celery leaves contain active compounds such as flavonoids and potassium that are believed to help lower blood pressure by relaxing blood vessels and increasing the excretion of sodium through urine.This community service activity was carried out in Purwodadi Village and aimed to increase public awareness, especially among families, regarding hypertension and its non-pharmacological management using natural ingredients that are easy to find and affordable. The method used involved health education through counseling and direct demonstrations of how to prepare and consume celery leaf boiled water. Participants were actively involved in learning how to select, clean, boil, and properly consume the celery leaf water as a herbal drink.The results of the activity showed a significant improvement in community knowledge and understanding related to hypertension and the benefits of using celery leaves as a traditional remedy. It is hoped that after this activity, the local community will be able to independently apply this knowledge and routinely use boiled celery water as a preventive measure to maintain normal blood pressure and reduce the risk of complications. This effort is part of promotive and preventive health services to improve the quality of life and promote a healthy lifestyle at the village level.